2013
DOI: 10.1021/la304034b
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Hyperbranched Polymer–Gold Nanoparticle Hybrids: Understanding the Effect of Polymer Coverage on Assembly Size and SERS Performance

Abstract: In the past few years, remarkable progress has been made in unveiling novel and unique optical properties of strongly coupled plasmonic nanostructures. However, the application of such plasmonic nanostructures in biomedicine remains challenging because of the lack of facile and robust assembly methods for producing stable nanostructures. Previous attempts to achieve plasmonic nanoassemblies using molecular ligands were limited by the lack of flexibility that could be exercised in forming them. Here, we report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 57 publications
0
71
0
Order By: Relevance
“…Previously, localized surface plasmon resonance (LSPR) spectroscopy revealed that the morphology of gold nanostars changed during storage [19]. Furthermore, both supporting electrolyte composition and concentration as well as surface functionalization with molecules such as PEG [24], PVP [25], PSS-PDD multilayers [26], and hyperbranched polymers [27] improved nanostar stability. These functionalized nanostructures provide excellent examples as to why nanostructure stability is important in analytical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, localized surface plasmon resonance (LSPR) spectroscopy revealed that the morphology of gold nanostars changed during storage [19]. Furthermore, both supporting electrolyte composition and concentration as well as surface functionalization with molecules such as PEG [24], PVP [25], PSS-PDD multilayers [26], and hyperbranched polymers [27] improved nanostar stability. These functionalized nanostructures provide excellent examples as to why nanostructure stability is important in analytical applications.…”
Section: Introductionmentioning
confidence: 99%
“…24 Size has been shown to vary with polymer content during fabrication, 2528 however, clusters made with HPG 3k -g-C 18 (5) or LPG 3k -g-C 18 (2) remained 80 nm, regardless of concentration (Figure S9), with core diameters of approximately 40 nm and 60 nm respectively. To strengthen potential HPG-mediated inter-droplet interactions, 29 a larger HPG with a molecular weight of 50 kg/mol, termed HPG 50k , was synthesized by increasing the ratio of glycidol-to-initiator in the polymerization reaction (Figure S1a).…”
Section: Resultsmentioning
confidence: 99%
“…Raman and FTIR spectroscopy-established techniques for in situ reaction monitoring-have been used to good advantage in polymerization processes (Gulari et al, 1984;Dey et al, 2013). We have utilized Raman in situ monitoring to determine the real time trajectory of monomer content in the reactor.…”
Section: In Situ Process Analysismentioning
confidence: 99%